When Does Blur Matter? A Narrative Review and Commentary. Issue 2 (3rd April 2022) - Horwood, Anna M.
ABSTRACT: Blur is the subjective awareness that the edges of a high contrast image are indistinct. The concept of blur is fundamental to the understanding of vision, accommodation, refractive error, concomitant strabismus, and asthenopia. It is easy for clinicians to believe that blur always needs to be avoided or resolved, or that everyone responds to blur similarly. This narrative review outlines the literature on blur and the accommodation to resolve it, and relates it to current clinical practice. Laboratory studies have traditionally been highly controlled, using expert observers, but more recent research using naïve participants suggests that variability and tolerance of blur are common and more widespread than often thought, especially in children and clinical groups. Objective and subjective responses can differ widely, and it cannot be assumed that because we expect accommodation to have occurred, that it always has. A deeper understanding of the role of blur and objective accommodation in vision, refractive error and strabismus may help us understand the variability that exists in clinical practice. We may use blur to help investigation and treatment but also be relaxed about what is normal. Many patients are led to believe that they should always achieve constant clear vision, when this is unrealistic. Although pathological blur must be identified and treated, normal everyday blur may become medicalized into "a problem" by well-meaning professionals.